Pengaruh Kerjasama Tim dan Komunikasi Terhadap Kinerja Karyawan PT Buana Armada Jaya - Akbar Rizal Bahari; Deby Santyo Rusandy; Iing Sri Hardiningrum (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
.This research discusses the Influence of Teamwork and Communication on Employee Performance. This research discusses Teamwork and Communication on employee performance at PT Buana Armada Jaya. The research aims to explain the influence of teamwork and communication on employee performance at PT Buana Armada Jaya. The sample for this research is employees who work at PT Buana Armada Jaya, numbering 40 employees. The analysis techniques used are validity tests, reliability tests, classical assumption tests, multiple linear regression. The results of the research are (1) Teamwork has a significant effect on the performance of PT Buana Armada Jaya employees. The results of this research prove that, if teamwork is good, employee performance will be better, because without good teamwork, it is difficult for companies to achieve optimal results. (2) Communication has a significant effect on the performance of PT Buana Armada Jaya employees. (3) Overall Simultaneous Teamwork and communication have a significant effect on the performance of PT Buana Armada Jaya employees.